An investigation of the impact of Canadian wildfires on US air quality using model, satellite, and ground measurements - Z. Xue; Z. Xue; N. Udaysankar; S. A. Christopher (Atmospheric Chemistry and Physics)
Canadian wildfires transport large concentrations of particulate matter into the US, leading to various effects on the surface temperature, the radiation balance, and visibility and exacerbating pollution-related respiratory conditions. Using a combination of surface, satellite, and numerical models, this study quantifies the increase in surface fine particulate matter (PM2.5) in the continental US due to long-range transported smoke from Canadian wildfires during a wildfire episode from 9–25 August 2018. As a widely used indicator of surface pollution levels, satellite-retrieved aerosol optical depth (AOD) can provide crucial information on columnar pollution mass. However, the daily spatial coverage of satellite AOD is restricted due to cloud cover. In order to quantify the daily changes in surface pollution, we fill in the AOD gaps by utilizing simulated 10 km spatial resolution AOD from a chemistry transport model (CTM). Meteorological variables influencing smoke transport were also integrated alongside the gap-filled AOD product to estimate surface PM2.5 using geographically weighted regression (GWR) and random forest (RF) models. The model with better performance was subsequently applied to quantify PM2.5 changes due to Canadian wildfires. To isolate the impact of Canadian wildfires, we calculate the surface PM2.5 ratio with and without Canadian fire sources by conducting two CTM simulations: one with Canadian wildfire emissions enabled and another with these emissions turned off. Our results show that Canadian wildfires caused a significant increase in surface PM2.5, contributing up to 28 µg m−3 (a 69 % increase) across different US Environmental Protection Agency (EPA) regions during the August 2018 wildfire event.